"A country to fall in love with/in": gender and sexuality in Swedish Armed Forces' marketing campaigns. Issue 2 (15th March 2019) - Strand, Sanna; Kehl, Katharina
ABSTRACT: Gender mainstreaming measures adopted by armed forces have gained scholarly attention for the ways in which they ascribe meaning and relevance to military institutions, perform national identities and order international politics. This article analyzes how gendered and sexualized subjectivities and symbols are mobilized in recent marketing campaigns launched by the Swedish Armed Forces (SAF). In these campaigns, Sweden is performed as a "progressive" nation/state whose citizens hold values, rights and freedoms considered "extreme in the eyes of others, " thus being in need of protection by the SAF. This notion of Swedish progressiveness—often constituted as equality between people of all sexual orientations and gender identities—is epitomized in the campaign slogan "Sweden, a country to fall in love with/in." This article probes how performative enactments of a gender-exceptional nation works within broader discursive terrains constituting a military institution undergoing large-scale transformations. We argue that constructions of a tolerant and modern Sweden (re)produce treacherous, single narratives of distant and dangerous Others and risk making invisible domestic discrimination on the basis of gender identity and sexual orientation, ultimately enabling the ongoing rearmament and reterritorialization of the SAF. Abbreviations: LGBT: Lesbian, gay, bisexual and transgender; SAF: Swedish Armed Forces